The Typology and Semantic Functions of Reporting Verbs in Online editorials of Philippine newspapers - Dizon, Brigette Olalia (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2021)
The purpose of this study is to examine and determine the typology and the semantic functions of the reporting verbs used in the editorial sections of five Philippine online newspapers. Quantitative analysis was assumed in procuring the frequency counts and percentages of the data to be analyzed while qualitative analysis was applied in analyzing and categorizing the typology and semantic characteristics of the reporting verbs. The corpus of the study involved online editorial sections of five Philippine newspapers. Reporting verbs were highlighted or marked each time they appeared in every reporting sentence from the online editorials. Manual tallying was employed in obtaining the frequencies. Afterwards, the reporting verbs underwent examination and categorization for its typology and semantic characteristics. Findings show that the reporting verbs discovered from the online editorial sections were divided into five semantic categories. These categories were as follows: communication verbs, mental verbs, activity verbs, causative verbs, and verbs of aspect. Also, most of the reporting verbs found were from the communication category. As regards the typology, results show that all online editorial sections from the five Philippine online newspapers employed and examined used a significant deal of reporting verbs which were considered as public in reporting information.